ANALISIS KEGAGALAN LUBRICATION SYSTEM AUXILIARY POWER UNIT (APU) PESAWAT - Perkasa, Syahmi; Rahmawati, Fajar Khanif (Institut Teknologi Dirgantara Adisutjipto, 2023)
The Boeing aircraft is the newest variant of the Boeing 737 aircraft. During operation, various problems will certainly be found. One of the problems that occurs is the failure of the APU Lubrication System. The right type of maintenance is needed to minimize or prevent failure. The method used is the Failure Mode and Effect Analysis (FMEA) and Risk Priority Number (RPN) methods. The first step is to identify failures in each component. each failure mode and failure effect that occurs in each component is translated into the FMEA table. The conclusion obtained is identification of failures that occur in the APU lubrication system, namely there are 22 failures in the APU lubrication system, 11 cases of Oil clog failure, 7 cases of Oil leak failure, 4 cases of Oil Temperatue failure. Failure cases that have a high critical failure modes are oil clog with an RPN value of 288 and oil leak with an RPN value of 256, while moderate critical failure modes is oil temperature with an RPN value of 168.